Tool use and action planning in apraxia - Sunderland, Alan; Wilkins, Leigh; Dineen, Rob (Neuropsychologia, 2011)
▸ Patients with apraxia often failed to invert the hand to grasp inverted tools. ▸ Ability to invert the hand to grasp abstract objects was largely unimpaired. ▸ For correct responses, rotation of the wrist was later during reaching for tools. ▸ These data suggest degraded access to tool-use representations in apraxia. ▸ But this cannot explain deficits in imitating or matching meaningless postures. Apraxia after left inferior parietal lesions has been widely interpreted as evidence of damage or impaired access to representations of tool-use, but most research has investigated pantomime of tool actions, not handling of actual tools. An alternative account is that inferior parietal damage does not affect tool-use representations but impairs cognitive processing about postural and hand-tool spatial relationships which is necessary for planning and controlling any complex action. Four apraxic patients and 10 age-matched controls were asked to reach rapidly for tools or abstract objects of similar dimensions. Under conditions of time pressure and divided attention, the patients frequently failed to invert the hand to grasp inverted tools by the handle, whereas ability to invert the hand to avoid a barrier and grasp abstract objects was largely unimpaired. Frequency of errors in tool grasping correlated with severity of apraxia. When inverted tools were correctly grasped, rotation of the wrist occurred later during the reaching movement than when inverting the hand to grasp an abstract object. These data are consistent with the theory of degraded access to tool-use representations in apraxia, but this theory cannot account for co-occurring deficits in imitating or matching meaningless hand or body postures.